Impact of asynchronism on GPU accelerated parallel iterative computations - Contassot-Vivier, Sylvain; Jost, Thomas; Vialle, Stéphane (HAL CCSD, 2010)
International audience We study the impact of asynchronism on parallel iterative algorithms in the particular context of local clusters of workstations including GPUs. The application test is a classical PDE problem of advection-diffusion-reaction in 3D. We propose an asynchronous version of a previously developed PDE solver using GPUs for the inner computations. The algorithm is tested with two kinds of clusters, a homogeneous one and a heterogeneous one.